Chipping performance of new processing varieties of potato (Solanum tuberosum) grown in cooler north-western plains - Marwaha, R S; Pandey, S K; Singh, S v (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted to determine the chipping quality, sucrose, free amino acids, phenols and soluble proteins in 2 newly released Indian processing varieties, viz ’Kufri Chipsona 1’ and ’Kufri Chipsona 2’, along with an old table variety ’Kufri Jyoti’ and 2 exotic American processing cultivars ’Atlantic’ and ’FL 1533’ during the autumn season of 2001-2002 and 2002-2003 at Jalandhar, Punjab. Observations were recorded at 3 different stages of tuber development, i e on 70,80 and 90 days after planting. Both ’Kufri Chipsona 1’ and ’Kufri Chipsona 2’ gave high tuber yield, more than 20% tuber dry-matter content, high chip yield, low chip oil content and acceptable chip colour at all the stages that were either better or at par with exotic cultivars. ’Kufri Jyoti’ showed poor processing traits. The mean contents of reducing sugar (2.87 and 2.27 mg/100g fresh weight) and total phenol (52.8 and 53.5 mg/100g fresh weight) were significantly lower and soluble protein (1087 and 1094 mg/100g fresh weight) higher in ’Kufri Chipsona 1’ and ’Kufri Chipsona 2’, respectively, than that of the exotic cultivars that are desirable characteristics for processing.